ANALISIS KESULITAN SISWA DALAM PEMECAHAN MASALAH MATEMATIKA PADA MATERI ARITMETIKA, ALJABAR, STATISTIKA, DAN GEOMETRI - risa mahdayani (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
The aim of this research is to describe the percentage of class IX students of SMPN at Yogyakarta City who get difficulties in terms of the types of difficulty based on solving problem steps in all math materials and based on each material such as arithmetics, algebra, statistics and geometry. This research is included in survey research with quantitative approaches. The research result suggests that at diagnostic test of all materials, the percentage of students who have reading difficulty is 47.4%, comprehension difficulty 51.5%, transformation difficulty 74.3%, process skill difficulty 80.4%, and encoding difficulty 80.4%. For arithmetics materials the reading difficulty is 52,.6%, comprehension difficulty 68.1%, transformation difficulty 94.8%, process skill difficulty 95.8%, and encoding difficulty 95.8%. As for algebra materials the reading difficulty is 61.8%, comprehension difficulty 65.9%, transformation difficulty 77.3%, process skill difficulty 80.4%, and encoding difficulty 80.4%. For the statistics materials the reading difficulty is 54.6%, comprehension difficulty 54.6%, transformation difficulty 83.5%, process skill difficulty 91.7%, and encoding difficulty 91.7%. For the geometry materials reading difficulty is 34.1%, comprehension difficulty 35.1%, transformation difficulty 51.5%, process skill difficulty 70.1%, and encoding difficulty 70.1%. Keywords: analysis of difficulties, difficulty of students, math problem solving